ISOLATION AND SCREENING OF AMYLOLYTIC PENICILLIUM SPECIES FROM SOIL - B. N. SWARGIARI; P. K. BARUAH (International Journal of Pharma and Bio Sciences, 2013)
Amylase is important industrial enzymes having a share of about 25-33% of the total global enzyme market. Amylases are commercially produced from bacteria and filamentous fungi especially from Bacillus and Aspergillus. Several Penicillium species are also known to produce amylases, certain species of which are also recognized as commercial producers. This study was aimed to isolate Penicillium species from different soil samples of Assam, India and to screen for the ability to produce amylase. A total of 25 Penicillium species were isolated and examined for amylase production ability. Out of the 25 isolates 11 isolates i.e., isolate nos. 1-11 showed good amylase activity in terms of clear zone formation. 7 isolates showed little activity and the rest 7 isolates had no activity. The 11 isolates found to be good in solid starch agar media were also screened in liquid media for amylase producing ability and observed that all the 11 isolates have the ample capacity to produce amylase. This study may generate interest in searching of new indigenous microbial sources for the production of various secondary metabolites like enzymes.